2019
DOI: 10.3390/ijerph16081445
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Social Capital, Social Capital Satisfaction, Self-Esteem, and Depression among Elderly Urban Residents: Analysis of Secondary Survey Data

Abstract: The role that psychological variables play in depression among elderly urban residents has received little research attention. Therefore, the purpose of this study was to examine the relationships between social capital, social capital satisfaction, self-esteem, and depression among elderly urban residents. We used the responses provided by 701 elderly persons to scales assessing social capital (i.e., network, trust), social capital satisfaction, self-esteem, and depression, as part of the Korea Welfare Panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 66 publications
1
26
0
2
Order By: Relevance
“…For instance, a study in Korea used trust and reciprocity to measure social capital and suggested that low trust and reciprocity levels were associated with depressive symptoms in older people [6]. Similarly, another study in Korea explored the relationship between social capital (measured with network and trust) and depression among urban older adults and found that trust in social capital was associated with depression, while network was not [14]. A study in China surveyed the association of social capital (assessed with trust, reciprocity, social network, and social participation) with depression among urban older people, and revealed that trust, reciprocity, and social network were significantly associated with depression while social participation was not [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study in Korea used trust and reciprocity to measure social capital and suggested that low trust and reciprocity levels were associated with depressive symptoms in older people [6]. Similarly, another study in Korea explored the relationship between social capital (measured with network and trust) and depression among urban older adults and found that trust in social capital was associated with depression, while network was not [14]. A study in China surveyed the association of social capital (assessed with trust, reciprocity, social network, and social participation) with depression among urban older people, and revealed that trust, reciprocity, and social network were significantly associated with depression while social participation was not [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, health is not only the absence of disease or pain; it is also the state of mental well-being. Previous studies have shown that mental illnesses such as anxiety [8], depression [9], schizophrenia [10], and emotional disorders [11,12] are becoming more and more serious. The Global Burden of Disease research reported that 20% of the population aged 60 years and over have psychological diseases, with anxiety and depression being the most common [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study in Korea used trust and reciprocity to measure social capital and suggested that low trust and reciprocity levels were associated with depressive symptoms in older people [6]. Similarly, another study in Korea explored the relationship between social capital (measured with network and trust) and depression among urban older adults and found that trust in social capital was associated with depression, while network was not [14]. A study in China surveyed the association of social capital (assessed with trust, reciprocity, social network, and social participation) with depression among urban older people, and revealed that trust, reciprocity, and social network were signi cantly associated with depression while social participation was not [11].…”
Section: Introductionmentioning
confidence: 99%